EMPLOYEES’ PRE-DISMISSAL RIGHT TO BE HEARD: THE MALAYSIAN AND THE ISLAMIC PERSPECTIVE (UUM Journal of Legal Studies, 2020)
It seemed to be a settled principle of law that before an employee can be dismissed from his job for misconduct, he must have a notice of the allegation against him and accorded a reasonable opportunity of being heard. However, this principle should be revisited in the light of two conflicting Federal Court’s decisions pertaining to the mandatory issue of this right especially in the private sector employment in Malaysia. The curable principle as enunciated by Dreamland Corporation (M) Sdn. Bhd. v Choong Chin Sooi & Anor [1988] 1 MLJ 111 has watered down the right of the employee to be heard as it was held in that case that the irregularity in holding a domestic enquiry is not fatal to the employer. He may justify the dismissal at the Industrial Court. Despite the existence of this principle, it should be emphasised that the right to a pre-dismissal hearing should be interpreted to be mandatory and not discretionary as there are two statutory provisions and constitutionally recognised rules of natural justice which may support this proposition. The mandatory effect of the domestic enquiry should be consistently upheld. With a view to enhance the employee’s right and to ensure harmonious employer-employee relationship, it would be the purpose of this article to comparatively examine and learn how the same right is treated and regulated under the Islamic principle of justice and its application in two Islamic countries, namely Kingdom of Saudi Arabia and the UAE. Apart from narrowing down the gap in the Islamic knowledge on the administration of justice in dismissal cases, this article may also contribute in idea on how to harmonise the current employment laws and the Sharia.